'Do you mean I'm not whole?': Exploring the role of support in women's experiences of mastectomy without reconstruction. (October 2018) - Archer, Stephanie; Holland, Fiona G; Montague, Jane
This study explores the role of others in supporting younger women who opt not to reconstruct their breast post-mastectomy. Semi-structured interviews were conducted with six women diagnosed with breast cancer in their 30s/40s. The women lived in England, had been diagnosed a minimum of 5 years previously and had undergone unilateral mastectomy. An interpretative phenomenological analysis revealed three themes: Assuring the self: 'I'll love you whatever', Challenging the self: 'Do you mean I'm not whole?' and Accepting the self: 'I've come out the other side'. The women's experiences of positive support and challenges to their sense of self are discussed.